Global Relationships Between River Width, Slope, Catchment Area, Meander Wavelength, Sinuosity, and Discharge. Issue 6 (25th March 2019) - Frasson, Renato Prata de Moraes; Pavelsky, Tamlin M.; Fonstad, Mark A.; Durand, Michael T.; Allen, George H.; Schumann, Guy; Lion, Christine; Beighley, R. Edward; Yang, Xiao
Abstract: Using river centerlines created with Landsat images and the Shuttle Radar Topography Mission digital elevation model, we created spatially continuous maps of mean annual flow river width, slope, meander wavelength, sinuosity, and catchment area for all rivers wider than 90 m located between 60°N and 56°S. We analyzed the distributions of these properties, identified their typical ranges, and explored relationships between river planform and slope. We found width to be directly associated with the magnitude of meander wavelength and catchment area. Moreover, we found that narrower rivers show a larger range of slope and sinuosity values than wider rivers. Finally, by comparing simulated discharge from a water balance model with measured widths, we show that power laws between mean annual discharge and width can predict width typically to −35% to +81%, even when a single relationship is applied across all rivers with discharge ranging from 100 to 50, 000 m 3 /s. Plain Language Summary: For years, scientists and engineers have been using aerial photography to study the shapes of rivers, how they change over time, and how they relate to other river characteristics, such as river width, the slope of the water surface, and flow. These studies served as basis for the development of theories describing erosion, sediment transport, the speed at which flood waves travel through a basin, and serving as guidance for the measurement of river flow. However, such studies were often conducted in person, or done by combining results from other authors, leading to a very limited coverage of world rivers, most of which were in North America. As images of world rivers obtained by satellites became available and adequate computational power became affordable, we were able to describe the shape of worldwide rivers and how other properties, such as slope, width, and flow relate to meander characteristics. We showed that although classical geomorphic studies had limited geographical coverage, their results could generally be applied to typical rivers over the world. Additionally, with our results, rivers with atypical meander characteristics can be better identified, allowing the advancement of our understanding of how rivers work. Key Points: Using satellite imagery, meander wavelength and sinuosity were computed globally for the first time Even when extended to global scales, classical relationships between river width and meander wavelength and discharge still hold We found strong associations between sinuosity, width, meander wavelength, slope, and discharge